Pediatric NAFLD Epidemiology, Risk Factors and Research Gaps in Uzbekistan and India - Dinmukhammadieva Dilorom Rakhimjan kizi; Saurav Sunil Pawshe; Shadiyeva Soadat Ulmasovna (Academia Open, 2026)
General Background: Pediatric Non-Alcoholic Fatty Liver Disease (NAFLD) represents a critical chronic liver condition in children globally, characterized by hepatic fat accumulation without alcohol exposure, potentially progressing to steatohepatitis, fibrosis, and cirrhosis. Specific Background: Rapid socioeconomic transitions in Asia have escalated childhood obesity rates, with India reporting prevalence estimates of 12–63% among overweight children, while Uzbekistan demonstrates 50–66% prevalence in similar cohorts, though comprehensive epidemiological data remain limited. Knowledge Gap: No comparative analysis exists examining pediatric NAFLD patterns between Uzbekistan and India, particularly regarding temporal trends and population-based prevalence. Aims: This study compares burden, risk factors, and clinical characteristics of pediatric NAFLD across both nations through systematic literature review. Results: Both countries exhibit increasing prevalence driven by obesity and insulin resistance, with male preponderance and age-dependent patterns; however, Uzbekistan lacks population-based studies unlike India's more established epidemiological framework. Novelty: This represents the first cross-country comparison of pediatric NAFLD between Central and South Asian contexts. Implications: Findings underscore urgent need for standardized screening protocols, culturally adapted lifestyle interventions, and population-based research in Uzbekistan to inform national health policies.Keywords : Pediatric NAFLD, Childhood Obesity, Non-Alcoholic Fatty Liver Disease, Metabolic Syndrome, Insulin ResistanceHighlight : Prevalence reaches 42-47% among overweight Indian children, with boys consistently more affected. Uzbekistan shows 50-100% rates in obese cohorts but lacks comprehensive population-based studies. Both nations face growing burden from dietary transitions, urbanization, and sedentary lifestyles.